The Influence of Radiotherapy on the Mechanical Properties of Silicone Breast Implants. Issue 7 (July 2018) - Bachour, Yara; Oei, Lisanne J.; Van der Veen, Albert J.; Vos, Bart E.; Louis, Andre; Heukelom, Stan; Ritt, Marco J. P. F.; Niessen, Frank B.; Koken, Phil W.; Winters, Hay A. H.
Abstract : Background: Silicone breast implants have been used for decades for cosmetic breast augmentation or reconstruction after mastectomy. In selected cases, postmastectomy adjuvant radiotherapy is given with the breast implants in situ. Previous clinical studies have shown that radiotherapy may lead to complications such as capsular contracture and infection and that removal of the implant may be required. Yet, the effect of radiotherapy on silicone breast implants themselves is unknown. The aim of this study was to investigate if irradiation of breast implants influences their mechanical properties. Methods: This was an ex vivo study on 32 ready-to-use silicone breast implants (Mentor and Silimed). Half of the implants of each brand were irradiated with 1 × 60 Gy, the other half were not irradiated. Tensile, mechanical hysteresis, and rheology tests were performed. Differences in mechanical properties between the irradiated and nonirradiated implants were determined. Results: No significant differences were found in tensile strength, mechanical hysteresis, and rheological properties between irradiated and nonirradiated implants. Conclusions: Breast implants' mechanical properties for these 2 brands were not significantly affected after single-dose irradiation in an ex vivo setting.